Conservative Management in A Case of Aplasia Cutis Congenita: Case Report - Niño Chacón, Martha Raquel; Rojas Rodríguez, Ingry Katerine (Iatreia, 2025)
Introduction: Aplasia cutis congenita is a condition of multifactorial etiology characterized by partial or total absence of skin or other structures of variable depth, including the periosteum. Objectives: To present a case of non-syndromic aplasia cutis congenita in the lower limbs in a newborn with no family or personal history, with conservative management. Methodology: An observational case report study was conducted, in which bone lesions were excluded. Vaseline-impregnated gauze was applied every 12 hours for three months, and follow-up was conducted via telephone throughout the treatment period. Results: During follow-up, complete epithelialization of the affected limb was observed, with color changes without functional impairment. Conclusions: Conservative management of these lesions improves the quality of life of patients and affected families, reducing hospital stay and the risk of bacterial resistance.